Overseas Study Experience and Students' Attitudes toward China: Evidence from the Beijing College Students Panel Survey. Issue 1 (2nd January 2018) - Li, Zhonglu; Feng, Shizheng
Abstract: Over the past decades, hundreds of thousands of Chinese students moved abroad, primarily to Western countries, to pursue their further education. Upon their return to China, these individuals were very likely to become academic, business, and/or political elites, and their knowledge, skills, attitudes, and beliefs were likely to have a significant influence on China's future development. This article examines how the experience of studying abroad changed these students' evaluation of China's development and prospects. Based on an analysis of panel data from the Beijing College Students Panel Survey, we reveal that the influence of overseas study on students' evaluation of China's overall current situation and future prospects follows a U shape, that is, students' attitudes toward China initially deteriorate after entering foreign universities, but after a certain point their evaluations tend to rebound. Exposure to foreign media has a similar effect on students' attitudes toward China. Students who are frequently exposed to foreign media tend to be more pessimistic about China's overall situation and future prospects. The implications of these findings are discussed.